Hubungan Kualitas Tidur Dengan Tingkat Konsentrasi Belajar Mahasiswa Fakultas MIPA Dan Kesehatan Universitas Muhammadiyah Riau - Razky Ihzanul Sably; Gasril, Pratiwi (Fakultas MIPA dan Kesehatan, Universitas Muhammadiyah Riau, 2022)
Good sleep quality will have a good influence on one's concentration ability while poor sleep quality can cause a decrease in concentration which can affect the quality of learning outcomes. The purpose of this study was to determine the relationship between sleep quality and the level of concentration of students in the Faculty of Mathematics and Natural Sciences and Health, University of Muhammadiyah Riau. This type of research is descriptive correlative research using a cross sectional study approach. This research was conducted on July 28 to August 12, 2022 at the Faculty of Mathematics and Natural Sciences and Health, Muhammadiyah University of Riau. The population in this study amounted to 696 people, the number of research respondents was 87 respondents. The sampling technique used is Stratified Random Sampling. The instrument used is a google form link questionnaire using a Likert scale. The results showed that there was a relationship between sleep quality and the level of learning concentration of students of the Faculty of Mathematics and Natural Sciences and Health, Muhammadiyah University of Riau with the results with a p value of 0.001 (pv 0.005). It is recommended for students to maintain good sleep quality so that they can concentrate well during the learning process so that they can follow the learning process to the maximum and quality.